A snap-shot of a diarrheal epidemic in Dhaka due to enterotoxigenic Escherichia coli and Vibrio cholerae O1 in 2022 - Tauheed, Imam; Ahmed, Tasnuva; Akter, Afroza; Firoj, Md Golam; Ahmmed, Faisal; Rahman, Sadia Isfat Ara; Afrad, Mokibul Hassan; Islam, Md Nazmul; Rahman, Aninda; Khan, Ashraful Islam; Alam, Baharul; Bhuiyan, Taufiqur Rahman; et al. (Frontiers in Public Health, 2023)
Background: Enterotoxigenic Escherichia coli (ETEC) and Vibrio cholerae O1 are most common bacterial causes of diarrheal diseases in Bangladesh. This analysis projected distribution of ETEC and V. cholerae O1 among diarrheal patients of icddr,b, Dhaka hospital in two diarrheal peaks of 2022. Methodology: Under 2% systematic surveillance system, stool samples collected from diarrheal patients of icddr,b hospital were cultured and diagnostic testing was done for ETEC and V. cholerae O1. Comparison of positive cases was done between first peak (March-April) and second peak (October-November) in 2022. Results: A total of 2,937 stool specimens were tested of which 12% were ETEC and 20% were V. cholerae O1. About 40% of the severe dehydration cases were infected with V. cholerae O1. Predominant ETEC enterotoxin type was ‘LT/ST’ (41%). The LT enterotoxin significantly increased from 13% to 28% in the second peak (p=0.015). The predominant colonization factors (CFs) on ETEC were CS5+CS6 (23%), followed by CS6 (15%). CF-positive isolates was significantly higher in the second peak (36%) than in the first peak (22%) (p=0.043). Total 14% cases were co-infected with ETEC and V. cholerae O1. Significant differences in the distribution of enterotoxin types were observed (p=0.029) among the co-infection cases. Conclusion: Changing patterns of enterotoxin and CFs observed in ETEC pathogens should be taken into consideration for ETEC vaccine development. Considering cholera and ETEC biannual trends in causing diarrheal epidemics and outbreaks, emphasizes the need for thoughts on combination vaccine strategies for preventing acute watery diarrhea due to the two major bacterial pathogens.